Prescribing or co-designing exercise in healthy adults? Effects on mental health and interoceptive awareness - Almarcha, Maricarmen; González, Ignacio; Balagué, Natàlia; Javierre, Casimiro (Frontiers in Behavioral Neuroscience, 2022)
Universal exercise recommendations for adults neglect individual preferences, changing constraints and their potential impact on associated health benefits. A recent proposal suggests replacing the standardised World Health Organisation (WHO) exercise recommendations for healthy adults by co-designed interventions where individuals participate actively in the decisions about the selected physical activities and the effort regulation. This study contrasts the effects on mental health and interoceptive awareness of a co-designed and co-adapted exercise intervention with an exercise program based on the WHO recommendations for healthy adults. Twenty healthy adults (10 men and 10 women, 40-55 y.o.) participated voluntarily in the research. They were randomly assigned to a co-designed exercise intervention (CoD group) and a prescribed exercise program (WHO group). Supervised online by specialised personal trainers, both programs lasted nine weeks and were equivalent in volume and intensity. The effects of the exercise intervention were tested through personal interviews, questionnaires (DASS-21 and MAIA) and a cardiorespiratory exercise test. Intragroup differences (pre-post) were assessed using the Mann-Whitney Wilcoxon test and intergroup differences through Student's t-tests. Effect sizes were calculated through Cohen's d. Interviews were analysed through thematic analysis. Eleven participants completed the intervention (CoD=8, WHO=5). Both groups improved, but non significantly, their cardiorespiratory testing results, and no differences were found between them post-intervention. Mental health was only enhanced in the CoD group (p<0.001), and interoceptive awareness improved in seven of the eight scales in the CoD group (p<.001) and only in 3 scales in the WHO group (p<.01). In conclusion, the co-designed intervention was more effective for developing mental health, interoceptive awareness, autonomy, and exercise self-regulation than the WHO-based exercise program.